2017
DOI: 10.5194/wes-2017-4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field Test of Wake Steering at an Offshore Wind Farm

Abstract: Abstract. In this paper, a field test of wake steering control is presented. The field test is the result of a collaboration between the National Renewable Energy Laboratory (NREL) and Envision Energy, a smart energy management company and turbine manufacturer. In the campaign, an array of turbines within an operating commercial offshore wind farm in China have the normal yaw controller modified to implement wake steering according to a yaw control strategy. The strategy was designed using NREL wind farm model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Schreiber et al (2017) 19 and Draper et al (2018) 20 used wind tunnel experiments and LES to show that P p ≈ 1.8 for a wind turbine in sheared freestream conditions. Fleming et al (2017) 6 found P p ≈ 1.4 for the Envision 4 MW turbine using LES and confirmed this value in a field experiment, although the number of data points beyond |γ| > 10 • were limited.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Schreiber et al (2017) 19 and Draper et al (2018) 20 used wind tunnel experiments and LES to show that P p ≈ 1.8 for a wind turbine in sheared freestream conditions. Fleming et al (2017) 6 found P p ≈ 1.4 for the Envision 4 MW turbine using LES and confirmed this value in a field experiment, although the number of data points beyond |γ| > 10 • were limited.…”
Section: Introductionmentioning
confidence: 78%
“…Kheirabadi & Nagamune (2019) 1 for a recent review). One wind farm control methodology which demonstrates potential in simulations 2,3 , lab experiments 4,5 , and field experiments [6][7][8][9] to increase collective turbine power production is wake steering, which entails the intentional yaw misalignment of turbines to deflect wake regions laterally away from downwind generators. The potential for wake steering to increase wind farm power production depends on the magnitude of wake interactions between the wind turbines, the magnitude of the wake deflection as a function of yaw misalignment, and the power production lost by the yaw misaligned turbines 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Static yaw control, in which upstream turbines intentionally misalign their rotors with incoming winds, has been proven as a promising approach to increasing power extraction, in numerical studies [25,26], but also in wind-tunnel tests [27,28] and full-scale field measurements [29,30]. Studies on dynamic yaw control however are much more scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated the opportunity for an increase of a percent or more in annual energy production, which would result in revenue gains for wind plant owner/operators. The potential improvement has gained significant interest from industry and has led to multiple field campaigns involving industry-laboratory collaboration to prove the technology performance (for an example of field-test results in an offshore wind application, see Fleming et al 2017).…”
Section: Figure 3 Organization Of A2e Focus Areas and Dependencies Between Themmentioning
confidence: 99%